Blended Learning Management Platform for Strategic Educational Management Using Activity-Based Learning Techniques and AI Technology to Enhance Educational Leadership Competencies - Phakamach, Phongsak; Seenonlee, Autsanee; Panjarattanakorn, Darunee; Onsampant, Samrerng (Journal of Education and Learning Reviews, 2025)
Background and Aim: The objectives of this research were: 1) to develop a blended learning management platform on strategic educational management using combined activity-based learning techniques and AI technology to enhance educational administrator competencies; 2) to evaluate the platform’s efficiency against the 80/80 criterion and determine the effectiveness index and learning achievement with the platform; and 3) to study the opinions of experts and learners regarding learning with the platform. Materials and Methods: This research employed a research and development methodology. The sample group consisted of 57 Master of Education students from Rajamangala University of Technology Rattanakosin, academic year 2024, using classrooms as the sampling unit. The target group comprised 10 educational innovation and technology experts, selected purposively. The research instruments included: 1) a learning achievement test; 2) an expert evaluation form for the platform’s quality; and 3) a questionnaire on learners’ opinions regarding the platform. Statistical methods used for data analysis were percentage, mean, standard deviation, and t-test. Results: The research findings revealed that the developed blended learning management platform on strategic educational management using combined activity-based learning techniques and AI technology to enhance educational administrator competencies had an efficiency of 81.23/82.46, which met the 80/80 standard criterion, and an effectiveness index of .8328. Learners who used the platform showed significantly higher post-learning achievement compared to pre-learning achievement at the .05 statistical significance level. The expert evaluation of the platform’s quality was at a high level, indicating that the platform is suitable for learners to enhance their educational administrator competencies. Learners also expressed high levels of satisfaction with the platform. Conclusion: The research resulted in an efficient blended learning management platform on strategic education management to enhance educational administrator competencies, which is practically applicable and facilitates learners’ development in strategic education management as designed.